The Limpopo Academy of Private Detection [large type] - McCall Smith, Alexander, 1948- (McCall Smith, Alexander, 1948- No. 1 Ladies Detective Agency series., 2012)
The formidable talents of Precious Ramotswe are put to the test in the face of a mysterious disciplinary problem at her adopted daughter's school, assistant Grace Makutsi's early marital adjustments, and the appearance of the No. 1 Ladies' hero detective.